Targeted review of maximum residues levels (MRLs) for indoxacarb. (9th August 2022) - ,; Bellisai, Giulia; Bernasconi, Giovanni; Brancato, Alba; Cabrera, Luis Carrasco; Castellan, Irene; Ferreira, Lucien; Giner, German; Greco, Luna; Jarrah, Samira; Leuschner, Renata; Magrans, Jose Oriol; et al.
Abstract: In compliance with Article 43 of Regulation (EC) No 396/2005, EFSA received a mandate from the European Commission to perform a targeted review of the maximum residue levels (MRLs) for indoxacarb based on Codex maximum residue limits (CXLs) or on import tolerances which might still be maintained after the expire of the approval of the active substance. EFSA screened the existing MRLs based on CXLs or on import tolerances considering the new toxicological reference values established during the peer review process for the renewal of the approval of indoxacarb and identified the MRLs for which an acute risk could not be excluded and several MRLs that are unlikely to pose a risk for consumers. Fall‐back MRLs could not be proposed for the commodities exceeding the new toxicological reference values as no further data were provided during the call for data. Therefore, risk managers may consider maintaining only the MRLs identified during the screening as safe for consumers. However, for some of the proposed MRLs, further consideration by risk managers is needed due to the uncertainties identified.